Glutamine synthetase in human carotid plaque macrophages associates with features of plaque vulnerability: An immunohistological study. (July 2022) - Sorto, Pia; Mäyränpää, Mikko I.; Saksi, Jani; Nuotio, Krista; Ijäs, Petra; Tuimala, Jarno; Vikatmaa, Pirkka; Soinne, Lauri; Kovanen, Petri T.; Lindsberg, Perttu J.
Abstract: Background and aims: Glutamine synthetase (GLUL), the sole generator of glutamine, is a metabolic nexus molecule also involved in atherosclerosis. We recently demonstrated a 2.2-fold upregulation of GLUL mRNA in stroke-causing carotid plaques when compared with plaques from asymptomatic patients. Here we compared in the same cohort GLUL mRNA expression with plaque gross morphology, and the colocalization of immunodetectable GLUL protein with histopathological changes and molecular and mechanical mediators linked to plaque development. Methods: Endarterectomy specimens from 19 asymptomatic and 24 stroke patients were sectioned longitudinally and immunostained for GLUL, CD68, α-smooth muscle actin, iron, heme oxygenase-1 and CD163, and graded semiquantitatively in every 1 mm 2 . The amounts of cholesterol clefts and erythrocytes were graded. The fibrous cap thickness within each 1 mm 2 area was measured. The association between the local pathological findings was analyzed by a hierarchical mixed modelling approach. Results: The previously found correlation between GLUL mRNA and clinical symptomatology was supported by the increased GLUL mRNA in diseased tissue and increased local GLUL immunoreactivity in areas with multiple different atherosclerotic changes. A longer symptom-to-operation time correlated with lower GLUL mRNA (Rs  = −0.423, p= 0.050) but few outliers had a significantly higher GLUL mRNA levels, which persisted throughout the post-symptomatic period. Plaque ulceration associated with 1.8-fold higher GLUL mRNA ( p= 0.006). Macrophages were the main GLUL immunoreactive cells. GLUL immunostaining colocalized with erythrocytes, iron, CD163, and heme oxygenase-1. The correlations between local variables were consistent in both asymptomatic and stroke-causing plaques. An inverse correlation was found between the fibrous cap thickness and local GLUL immunoreactivity ( p= 0.012). Considerable variability in interplaque expression pattern of GLUL was present. Conclusions: Our results link connect macrophage GLUL expression with carotid plaque features characterizing plaque vulnerability. Graphical abstract: Image 1 Highlights: Glutamine synthetase (GLUL) is one of the oldest enzymes and the sole generator of glutamine in humans. Glutamine is one of the amino acids associated with cardiovascular disease outcomes. The ability to express GLUL by macrophages is linked to their inflammatory (M1-M2) phenotype. GLUL enzyme is expressed in multiform pattern by macrophages and macrophage foam cells in plaques. GLUL enzyme colocalizes with erythrocytes and iron within the plaques, but not consistently. Higher local GLUL immunoreactivity correlates with thinner fibrous cap in the same plaque areas.